Service recovery, customer satisfaction and customer loyalty: Evidence from Malaysia’s hotel industry - Cheng, Boon Liat *; Gan, Chin Chuan *; Imrie, Brian C.; Shaheen, M. (Emerald, 2019)
Purpose – The purpose of this study is to investigate the impact of service recovery dimensions on customer satisfaction and, subsequently, on customer loyalty in the context of the hotel industry. Design/methodology/approach – A self-administered questionnaire was distributed to 500 respondents who had the experiences of staying in the hotels in Malaysia. The structural equation modelling technique was used to study the relationship between the model and the developed hypotheses. Findings – The findings revealed that service recovery dimensions are significantly related to customer satisfaction and have a positive relationship between customer satisfaction and customer loyalty. Practical implications – As the main sector in the hospitality business, hotels play a vital role in the tourism industry. Therefore, the developments in tourism and hotels go hand in hand, as they are mutually dependent on each other. With significant yearly developments in the tourism industry and at a constant rate, hotel operators should reconsider their business strategies to achieve customer loyalty and sustain their businesses. In view of that, the findings of this study not only benchmarks better hotel services but also provides an improved understanding of service recovery that will effectively aid hotel operators in handling service failures; otherwise, customer dissatisfaction may occur if poor service recovery strategies are implemented. Originality/value – The intense competition in the service industry has driven companies to place extra attention on service recovery so as to ensure continuous success. With a yearly significant development in the tourism industry at a constant rate, hotel providers (one of the major beneficiaries) are driven to reconsider their business strategies to achieve customer loyalty and sustain their business.